Effects of an 8-week training program on the physical condition, emotional status, and mucosal immunity in adolescent swimmers - Zafeiriadis, S.; Loupos, D.; Tsalis, G.; Taitzoglou, I.; Mougios, V. (Asian Journal of Sport & Exercise Science, 2014)
The aim of the present study was to examine the relationship between intense training and the salivary lysozyme concentration in adolescent swimmers in conjunction with an assessment of emotional status. Fifteen male adolescent swimmers followed an 8-week training program up to a race. The blood lactate concentration, velocity at a blood lactate concentration of 4 mmol/l (V4), and maximal velocity (Vmax) were measured to observe changes in physical condition during the training procedure. Physical condition was evaluated through swimming trials of 3 x 100 m with progressively increasing intensity. The emotional status was evaluated by the Spielberger State Trait Anxiety Inventory (STAI), and innate mucosal immunity was evaluated by determining the salivary lysozyme concentration at five time points up to the final race. The post-exercise peak blood lactate concentration was higher on day 55 (13.5 2.8 mmol/l, mean SD) compared to days 1 and 23 (11.7 1.2 and 11.5 1.2 mmol/l, respectively, p < .05), when the changes at V4 and Vmax were not significant (p = 0.473 and p = 101, respectively). The STAI score increased just before the race (43.9 10.6) compared to days 1, 35, and 45 (35.0 5.7, 37.4 8.9, and 37.9 9.0, respectively, mean SD, p < .05), whereas salivary lysozyme concentration decreased just before the race (1.61 1.01 ng/ml) compared to days 1 and 35 (3.64 2.18 and 3.19 1.34 ng/ml, respectively, mean SD, p < .05). We conclude that race expectation increased the STAI score and decreased the salivary lysozyme concentration. It is possible that a stressful condition may alter the mucosal immunity and affect the emotional status of the athletes in contrast to a prolonged training program, which may not have such a radical effect.